2022
DOI: 10.3389/fpls.2022.1016822
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome profiling reveals the role of phytohormones and phenylpropanoid pathway in early-stage resistance against powdery mildew in watermelon (Citrullus lanatus L.)

Abstract: Yield and fruit quality loss by powdery mildew (PM) fungus is a major concern in cucurbits, but early-stage resistance mechanisms remain elusive in the majority of cucurbits. Here, we explored the comparative transcriptomic dynamics profiling of resistant line ZXG1755 (R) and susceptible line ZXG1996 (S) 48 h post-inoculation in watermelon seedlings to check precise expression changes induced by Podosphaera. xanthii race ‘2F’. Phenotypic responses were confirmed by microscopy and endogenous levels of defense a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…A precedent set by a wheat study elucidates the accumulation of transcripts from monolignol genes in the resistant strains upon PM infection [ 18 , 50 , 51 ]. This pattern echoes in instances such as watermelon powdery mildew interactions, where there is a conspicuous upregulation of genes related to defense mechanisms [ 36 ]. Our research findings shed light on the amplified expression of PAL genes in the R_all vs. R_0 comparison.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…A precedent set by a wheat study elucidates the accumulation of transcripts from monolignol genes in the resistant strains upon PM infection [ 18 , 50 , 51 ]. This pattern echoes in instances such as watermelon powdery mildew interactions, where there is a conspicuous upregulation of genes related to defense mechanisms [ 36 ]. Our research findings shed light on the amplified expression of PAL genes in the R_all vs. R_0 comparison.…”
Section: Discussionmentioning
confidence: 70%
“…It is noteworthy that this finding resonates with previous transcriptomic explorations conducted with cucumber, watermelon, and tobacco. These antecedent investigations similarly unveiled that resistant strains tend to manifest an enhanced DEG expression profile when juxtaposed with their susceptible counterparts during the ordeal of biotic stress [ 33 , 34 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that low-temperature stress regulated the transcript levels of genes related to phenylalanine metabolism, the phytohormone ethylene, photosynthesis, flavonoid accumulation, lignin synthesis, cells, cycleactive gibberellin, and salicylic acid (SA) signaling in cucumber seedlings. Yadav [ 46 ] employed transcriptome sequencing to identify genes related to phytohormones and found that the phenylpropanoid pathway was involved in resistance to powdery mildew disease in watermelon. Genes related to the phenylpropanoid pathway were transcriptionally up-regulated in resistant cucumber lines.…”
Section: Discussionmentioning
confidence: 99%